Tingkat Pengetahuan Mahasiswa DIII Farmasi Stikes Muhammadiyah Klaten Terhadap Covid – 19 - Muchson Arrosyid; Rahmi Nurhaini; Rosi Nur Indahsari (Universitas Muhammadiyah Klaten, 2021)
The Covid-19 pandemic is the event of the 2019 coronavirus disease spreading around the world. The role of the level of knowledge is very important to be able to determine decisions in a person's behavior so that it can be a strong basis for suppressing the number of Covid-19 infections so that they do not increase. The purpose of this study was to determine the level of knowledge of DIII Pharmacy students of STIKES Muhammadiyah Klaten against Covid-19. This research uses descriptive research method, the sampling technique used is Proportionate Stratified Random Sampling where the sample used is DIII Pharmacy students of STIKES Muhammadiyah Klaten as many as 68 respondents. The data collection tool in this research is a questionnaire and the data analysis used is univariate. The results showed that the knowledge of DIII Pharmacy students of STIKES Muhammadiyah Klaten on Covid-19 for the high category was 75%, the medium category was 23.5%, and the less category was 1.5%. Based on the characteristics of respondents with high knowledge, namely at the age of 19 years (25%), female gender (63.2%), and level II (26.5%).